The Development Of Problem Based Learning Modeling By Using Environmental To Improve Mastery Learning At Junior High School - Kurniawan Kurniawan; Arismunandar Arismunandar; Abdul Haling (Journal of Strategy and Transformation in Educational Management, 2024)
This study aims to: 1) Know the description of the needs analysis of the development of environment-based mathematics learning models in junior high schools / MTs so far; 2) Obtain comprehensive information in designing environment-based mathematics learning models to improve learning outcomes in junior high schools; 3) Produce products in the form of model books and environment-based mathematics learning tools that are valid to improve learning outcomes in junior high schools; 4) Produce products in the form of model books and environment-based mathematics learning tools that are practical to improve learning outcomes in junior high schools; 5) Produce products in the form of model books and environment-based mathematics learning tools that are effective for improving learning outcomes in junior high schools. The subjects of this research were students and teachers of MTs. Aisyiyah Sungguminasa. The research and development procedure used is the 4-D (Four-D) model, namely Define, Design, Develop and Disseminate. The data collection techniques used were observation, interview, test, questionnaire and documentation. The research instruments used learning implementation observation instruments, student learning outcomes assessment test instruments, and learning device validation sheets. The data analysis technique was carried out by (1) analyzing the level of validity, (2) analyzing the level of practicality, and (3) analyzing student and teacher response data. The results of this study indicate the need for the development of an environment-based mathematics learning model to improve learning outcomes at MTs. Aisyiyah Sungguminasa. The validation test results showed that the model book, learning tools and several research questionnaires were declared very valid based on expert assessments. Furthermore, the results of the practicality test also stated that this model proved to be very practical based on the results of observations of learning implementation and teacher and student response questionnaires.